Empirical review on innovation-performance linkage in Malaysian manufacturing SMEs - Zakaria, Nazlina; Chew Abdullah, Nor Azimah; Yusoff, Rushami Zien (EconJournals, 2016)
SMEs have demonstrated significant impact on the overall economic performance of Malaysia. Nevertheless, it has not reached their full potential.It is vital to comprehend its drivers in order to improve the production of SMEs. Previous studies discovered that organizations with better innovative behavior often instigate changes which could influence organizational’s performance. Hence, this study seeks to explore the relationship between organizational innovation and organizational performance of Malaysian SMEs. For that reason, this article does not only analyze the concept of organizational innovation and organizational performance, but also the linkage between both concepts at the end of the findings. Data from SMEs in manufacturing sectors were collected. Data from the respondents were assembled using a total of 321 self-administered questionnaires.The hypotheses were tested using Smart PLS 2.0.As a conclusion, a positive relationship was displayed between organizational innovation and organizational performance.This study will be helpful for future researchers, entrepreneurs and policy makers in grasping the value of organizational innovation towards boosting SMEs performance.